(untitled) (Journal of the College of Basic Education, 2022)
Since the language represents the beating heart in the body of the nation, and the blood that flows in its arteries so that life lasts for it, so as soon as a new generation is born, there are notable people among them who have vowed themselves, devoted their efforts, and sincere intentions to serve this nation and its children by preserving its identity and the continuity of its existence represented in the language. Al-Alam Al-Shintmari was one of those distinguished.Due to the importance of Diwan Zuhair, Al-Alam is considered one of the most important of those concerned with explaining Diwan Zuhair, which in its entirety includes praise and pride. Wisdom crowns this poetry with an aura of dignity that reflects the poet’s own personality.